A technoeconomic analysis of perovskite solar module manufacturing with low-cost materials and techniques. Issue 6 (19th May 2017) - Song, Zhaoning; McElvany, Chad L.; Phillips, Adam B.; Celik, Ilke; Krantz, Patrick W.; Watthage, Suneth C.; Liyanage, Geethika K.; Apul, Defne; Heben, Michael J.
Abstract : This technoeconomic analysis shows that perovskite solar cells can emerge as a cost leader in photovoltaic power generation. Abstract : After rapid progress in the past few years, emerging solar cells based on metal halide perovskites have become a potential candidate to rival and even outperform crystalline silicon photovoltaics (PV) in the marketplace. With high material utilization, easy manufacturing processes, and high power conversion efficiencies >20%, many experts anticipate that perovskite solar cells (PSCs) will be one of the cheapest PV technologies in the future. Here we evaluate the economic potential of PSCs by developing a bottom-up cost model for perovskite PV modules fabricated using feasible low-cost materials and processes. We calculate the direct manufacturing cost (31.7 per m 2 ) and the minimum sustainable price (MSP, 0.41 per Wp ) for a standard perovskite module manufactured in the United States. Such modules, operating at 16% photoconversion efficiency in a 30-year, unsubsidized, utility-level power plant, would produce electricity at levelized cost of energy (LCOE) values ranging from 4.93 to 7.90 ¢ per kW per h. We discuss limitations in comparing calculated MSPs to actual market prices, determine the effect of module lifetime, examine the effects of alternative materials and constructions, and indicate avenues to further reduce the MSP and LCOE values. The analysis shows that PSCs can emerge as a cost leader in PV power generation if critical remaining issues can be resolved.